The Development and Economic Impact of Railway in Batavia, 1873-1930 - Bandarsyah, Desvian; Abdulhadi, Abdulhadi; Sulaeman, Sulaeman (Paramita: Historical Studies Journal, 2022)
This study aims to determine the background of rail transportation modes developed in Batavia, focusing on the process, the activities between 1873 and 1930, and their economic impact in 1930. It was discovered that the increase in agricultural and plantation yields during the Cultivation Era led caused serious problems in transporting agricultural products from the plantation area to the port. It led to the construction of the first train connecting Batavia to Buitenzorg, operated by the Nederlandsche-Indische Spoorweg Maatschappij (NISM) on 31 January 1873. Another railway company, Staatsspoorwegen (SS), designed to operate the western route, including Batavia – Tanjung Priok, was inaugurated in 1885. It was followed by Batavia – Anyer in 1900 with a Duri – Tangerang branch in 1899 and Bataviasche Ooster Spoorweg Maatschappij (BOSM), which opened the eastern route, Batavia – Bekasi – Karawang, in 1891. Moreover, there is also the Batavia horse tram operated by Bataviasche Tramweg Maatschappij (BTM) in 1869, which served as the beginning of the history of the railroad in Batavia. It was also discovered that the train significantly impacted all economic actors in Batavia, including the farmers, traders, and industries. Penelitian ini bertujuan untuk: mengetahui latar belakang pembangunan moda transportasi kereta api di Batavia, proses pembangunan moda transportasi kereta api di Batavia dan perkembangan perkeretaapian di Batavia pada 1873-1930 serta dampak moda transportasi kereta api terhadap perekonomian Batavia 1930. Hasil penelitian ini bahwa terjadinya peningkatan hasil pertanian dan perkebunan pada era Tanam Paksa yang jumlahnya belipat-lipat menyebabkan masalah yang cukup serius bagi pengangkutan hasil perkebunan dan pertanian dari daerah perkebunan ke pelabuhan. Untuk mengatasi permasalahan-permasalahan itu, maka dibangunlah kereta api pertama di Batavia yang menghubungkan Batavia dengan Buitenzorg yang dioperasikan oleh Nederlandsche-Indische Spoorweg Maatschappij (NISM) pada 31 Januari 1873. Selanjutnya terdapat perusahaan kereta api lainnya yang turut beroperasi di Batavia, yaitu Staatsspoorwegen (SS) yang mengoperasikan lintas barat, meliputi Batavia – Tanjung Priok diresmikan tahun 1885, Batavia – Anyer 1900 dengan cabang Duri – Tangerang tahun 1899 dan Bataviasche Ooster Spoorweg Maatschappij (BOSM) yang membuka lintas timur, Batavia – Bekasi – Karawang tahun 1891. Tak lupa juga terdapat trem kuda Batavia yang dioperasikan oleh Bataviasche Tramweg Maatschappij pada tahun 1869 yang mengawali sejarah berdirinya sejarah kereta api di Batavia. Dengan ini kereta api mampu memberikan dampak ekonomi bagi seluruh pelaku ekonomi di Batavia, mulai dari petani, pedagang hingga industri sekalipun. Cite this article: Bandarsyah, D., Abdulhadi, Sulaeman. (2022). The The Development and Economic Impact of Railway in Batavia, 1873-1930. Paramita: Historical Studies Journal, 32(2), 159-170. http://dx.doi.org/10.15294/paramita.v32i2.31683